Proxel-based simulation of queuing systems with attributed customers. (12th April 2010) - Krull, Claudia; Xu, Wenjing; Horton, Graham
This paper describes a state space-based simulation method for queuing systems with attributed customers. Motivation was the need for exact solutions of queuing systems where no analytical solution is available. The original Proxel-based queuing simulation method is extended to incorporate attributed customers, concentrating on efficient coding and storage strategies to dampen state space explosion. The attributes classes priority, deadline and processing time are implemented and tested. Some interesting result statistics obtained would be hard to obtain using traditional simulation methods. The presented method can yield deterministic results for a larger number of queuing systems that cannot easily be solved analytically.